Sexually Dimorphic Accumulation of Persistent Organic Pollutants in Fetuses - Björvang, Richelle D.; Mamsen, Linn Salto (Frontiers in Toxicology, 2022)
Living in an industrialized era, we are exposed to man-made chemicals including persistent organic pollutants (POPs). Previous studies have shown associations of POP exposure with adverse outcomes in humans, wildlife, and the environment, making it a global concern. Exposure during sensitive windows of susceptibility such as fetal development is of particular concern because of the potential increased risk of developing diseases in childhood and adulthood. However, there are limited studies on the sexual dimorphism of POP accumulation during the prenatal period. In this mini-review, we focus on differences in POP concentrations in the placenta and fetal tissues between males and females. We also show the sexually dimorphic adverse outcomes of prenatal exposure to POPs. Overall, our summary shows that males may accumulate higher concentrations of POPs in the placenta and fetal tissues compared to females, although studies are sparse and inconsistent. In addition, there are differences in adverse health outcomes associated to prenatal POP exposure according to sex. Hence, we highly urge researchers investigating the health effects of POP exposure to consider sexual dimorphism in their studies.